Experimental Study on the Rheological Property of Aqueous Solution of Polyacrylamide - Wang, P.; Liu, Y.; Shen, S.Q. (Asian Journal of Chemistry, 2014)
With polyacrylamide solution as experimental subject, the paper reports the effect of mass concentration, shear rate and temperature on the rheological properties of polyacrylamide solution. Experimental results indicated that the apparent viscosity of polyacrylamide solution increased linearly with linear increasing concentration at concentration of 0.5-2.0 g/L; the apparent viscosity decreased with the increasing of shear rate and temperature. With the changing of temperature and concentration, the flow behaviour index (n) and consistency coefficient (K) behave similar to power-law fluid. Considering the combined effects of temperature and concentration, the experiment fitted an equation of the apparent viscosity with regard of concentration and temperature.